Community and Conviviality? Informal Social Life in Multicultural Places. (February 2019) - Neal, Sarah; Bennett, Katy; Cochrane, Allan; Mohan, Giles
This article contributes to understandings of the conviviality which has dominated recent sociological approaches to urban multiculture. The article argues for conviviality's conceptual extension by reference to recent rethinking of community as a profound sociality of 'being with' and a culture of urban practice. The article draws from a qualitative dataset examining sustained encounters of cultural difference and the relationships within social leisure organizations in three different English urban geographies. The article explores how the elective coming together of often ethnically diverse others, over time, in places, to do leisure 'things' meant these organizations could work as generative spaces of social interaction and shared practice through and in contexts of urban difference. The article concludes that putting conviviality as 'connective interdependencies' into dialogue with community as 'being in common' develops their sociological and explanatory power and counters the reductions and limitations that are associated with both concepts.